Kinetics Study on Carrier Injection‐Induced Degradation and Regeneration at Elevated Temperature in p‐Type Cast‐Monosilicon Passivated Emitter Rear Contact Solar Cells. Issue 7 (22nd April 2021) - Hu, Zechen; He, Qiyuan; Yuan, Shuai; Lin, Dehang; Song, Lihui; Yu, Xuegong; Yang, Deren
Abstract : Herein, the degradation and regeneration processes of p‐type cast‐monosilicon passivated emitter rear contact solar cells are investigated, by taking open‐circuit voltage as a measure for the light‐ and elevated‐temperature‐induced degradation (LeTID) and regeneration extent. Degradation and regeneration are triggered by current injection and light soaking at the same temperatures. Then, an Arrhenius plot, derived from the proposed model, is used to extract the degradation and regeneration rate constants of LeTID during both current injection and light‐soaking processes. The activation energies of degradation processes are calculated to be (0.790 ± 0.064) and (0.828 ± 0.013) eV for current injection and light soaking, respectively. The corresponding activation energies for regeneration processes are (1.059 ± 0.112) and (1.179 ± 0.070) eV, respectively. Notably, the similar activation energies indicate that the root cause of the LeTID induced by current injection or light soaking is the same. In addition, an exponential dependence of the rate constants upon the injection current values during the whole degradation and regeneration cycle induced by current injection is observed. These results are not only significant for understanding the kinetics of LeTID but also can shed light on effective LeTID suppression method in the photovoltaic industry. Abstract : The kinetics of light‐ and elevated‐temperature‐induced degradation (LeTID) in p‐type cast‐monosilicon passivated emitter rear contact solar cells are studied. It is found that the root cause of LeTID induced by light soaking or current injection is the same as confirmed by similar activation energies. Furthermore, the activation and deactivation of LeTID defects require injected excess carriers to participate.